2021
DOI: 10.1103/physrevlett.126.021802
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Waves and Proton Decay: Complementary Windows into Grand Unified Theories

Abstract: Proton decay is a smoking gun signature of Grand Unified Theories (GUTs). Searches by Super-Kamiokande have resulted in stringent limits on the GUT symmetry breaking scale. The largescale multipurpose neutrino experiments DUNE, Hyper-Kamiokande and JUNO will either discover proton decay or further push the symmetry breaking scale above 10 16 GeV. Another possible observational consequence of GUTs is the formation of a cosmic string network produced during the breaking of the GUT to the Standard Model gauge gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 88 publications
2
39
0
Order By: Relevance
“…Different string models have been compared in [35]. The possible connection of the NANOGrav results with GUT models and high-scale leptogenesis has also been studied in [36][37][38][39], and effects of low-scale leptogenesis on the SGWB were considered in [40]. Note that, independent of grand unification, a SGWB form a cosmic string network is a very interesting and well motivated signature of physics beyond the Standard Model [41][42][43][44].…”
Section: Jhep04(2021)168mentioning
confidence: 99%
“…Different string models have been compared in [35]. The possible connection of the NANOGrav results with GUT models and high-scale leptogenesis has also been studied in [36][37][38][39], and effects of low-scale leptogenesis on the SGWB were considered in [40]. Note that, independent of grand unification, a SGWB form a cosmic string network is a very interesting and well motivated signature of physics beyond the Standard Model [41][42][43][44].…”
Section: Jhep04(2021)168mentioning
confidence: 99%
“…Most distinguishable feature of GW emission from cosmic string is prediction of a strong signal across a wide range of frequency which has triggered a growing interest in this JHEP05(2021)211 field [76][77][78][79][80][81][82][83][84][85][86]. This also includes recent studies to probe GUT [87,88], high scale leptogenesis [89], low scale leptogenesis [90]. Unequivocally, GW probe of BSM models has become more interesting after the new NANOGrav analysis of 12.5 yrs pulsar timing data [91] which reports a strong evidence for a stochastic common-spectrum process and may be interpreted as a GW signal at frequency f ∼ 1/yr.…”
Section: Introductionmentioning
confidence: 97%
“…All breaking chains from SO (10) to G SM are listed in table 1 and 2. In our previous paper [24], we classified these chains into four categories: The formation of topological defects is ubiquitous in Grand Unified Theories. These defects are formed during the breaking of a larger gauge symmetry G I to a smaller one, G I−1 ⊂ G I .…”
Section: The So(10) Gut Frameworkmentioning
confidence: 99%
“…In our recent paper [24], we demonstrated the non-trivial complementarity between the observation of proton decay and gravitational waves in assessing the viability of SO (10) GUT breaking chains. We showed that future non-observations could exclude SO (10) breaking via flipped SU(5) × U(1) or standard SU (5), while breaking via a Pati-Salam intermediate symmetry [25], or standard SU(5) × U(1), may be favoured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation